Acute Pulmonary Embolism: From Morphology to Function - Mayo, John; Thakur, Yogesh (Seminars in Respiratory and Critical Care Medicine, 2014)
This article reviews the current diagnostic strategies for patients with suspected pulmonary embolism (PE) focusing on the current first choice imaging modality, computed tomographic pulmonary angiography (CTPA). Diagnostic strengths and weaknesses and associated cost-effectiveness of the diagnostic pathways will be discussed. The radiation dose risk of these pathways will be described and techniques to minimize dose will be reviewed. Finally the impact of new dual energy applications which have the potential to provide additional functional information will be briefly reviewed. Imaging plays a vital role in the diagnostic pathway for clinically suspected PE. CT has been established as the most robust morphologic imaging tool for the evaluation of patients with suspected PE. This conclusion is based on the high diagnostic utility of CT for the detection of PE and its unique capacity for accurate diagnosis of conditions that can mimic the clinical presentation of PE. Although current cost-effectiveness evaluations have established CT as integral in the PE diagnostic pathway, failure to acknowledge the impact of alternate diagnosis represents a current knowledge gap. The emerging dual energy capacity of current CT scanners offers the potential to evaluate both pulmonary vascular morphology and ventilation perfusion relationships within the lung parenchyma at high spatial resolution. This dual assessment of lung morphology and lung function at low (< 5 millisievert) radiation dose represents a substantial advance in PE imaging.
Keywords: CTPA; pulmonary embolism; acute PE; dual-energy CT; thoracic CT